Pengaruh Penerapan Metode Embelajaran Kooperatif Terhadap Prestasi Belajar PAI Siswa Kelas VII MTs. Darul Ulum Budi Agung Titi Papan - Mohammad Ilham Nasution; Parianto Parianto; Nurdiani Nurdiani (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to examine the effect of implementing cooperative learning with ‘Make a Match' methods on the Islamic Education (PAI) learning achievement of seventh-grade students at MTs Swasta Darul Ulum Budi Agung Titi Papan. The background of this study highlights that traditional teacher-centered approaches often limit student engagement, which in turn affects academic outcomes. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of seventh-grade students assigned to an experimental group and a control group. Data were collected using a PAI achievement test and classroom observation sheets. Inferential statistical analysis was conducted to determine significant differences between groups. The findings indicate that the cooperative learning method has a significant and positive effect on students' learning achievement. Therefore, cooperative learning is recommended as an effective instructional strategy to enhance students' understanding and performance in Islamic Education.